Distance Learning: Quality of Life and Familial Considerations - Gerbrandt, Marshall (International Journal of E-Learning & Distance Education / Revue internationale de l’apprentissage en ligne et de l’enseignement à distance)

(untitled) (AU Press, 2025)
The Canadian military is a large organization that relies upon people to accomplish a variety of tasks. While individual experience might differ, the idea that one needs to continue to learn as they advance within an organization is neither unique to the military nor novel. However, the Canadian military differs from most institutions in two ways. First, they design and deliver almost all their own training and education. Second, most training and education tends to occur elsewhere, which increases the time one spends away from home. Given current issues with recruitment and retention within the military, an issue common in many, it is important to consider how increasing the use of distance learning (DL) might contribute to a reduction in time away. Yet, simply increasing DL without recognizing how this might affect family and partner relationships may not be the solution. This paper describes qualitative research focused on understanding individual perceptions regarding increased DL with a particular focus on what this might mean for the quality of life of military members and their families.